Limitations of the Available Forms of Taxation for Corporate Entities in Poland Under the Pending COVID-19 Pandemic Threat - Dominika FLOREK (Communications of International Proceedings, 2021)
The paper provides analytical evaluations of changes stipulated by the planned introduction of revisions in the use of flat tax mechanisms available in Poland. In the intention of the legislator, the postulated modifications to the Polish taxation system are expected to tighten up the existing mechanisms and stimulate an effective increase in state budget revenues. The need is proclaimed to be dictated by the observable reduction of state revenues resulting from the COVID-19 pandemic. Based on analytical and critical evaluations of the existing legislative regulations of corporate taxation in Poland against those suggested by the legislator, the author provides an overview of potential consequences that may arise from such a revision from a taxpayer’s position. The evaluations are supplemented by results of a pilot study presenting responses from service sector enterprises to the scope of changes suggested in the revised tax law, particularly the elimination of the flat tax rate instrument.
Keywords: Taxation; Tax Regime; Entrepreneur